2022
DOI: 10.3390/toxins14020067
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A in Slaughtered Pigs and Pork Products

Abstract: Ochratoxin A (OTA) is a mycotoxin that is produced after the growth of several Aspergillus and Penicillium spp. in feeds or foods. OTA has been proved to possess nephrotoxic, hepatotoxic, teratogenic, neurotoxic, genotoxic, carcinogenic and immunotoxic effects in animals and humans. OTA has been classified as possibly carcinogenic to humans (Group 2B) by the IARC in 2016. OTA can be mainly found in animals as a result of indirect transmission from naturally contaminated feed. OTA found in feed can also contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 176 publications
(257 reference statements)
0
18
0
Order By: Relevance
“…Pigs are one of the most sensitive animals, OTA is frequently detected in various pork products made from pig organs such as the kidneys and livers. [ 5 ] How to prevent pigs from being violated by OTA exposure has become a common issue faced by farmers all over the world. Thus, we choose the porcine kidney 15 (PK‐15) cells as the cell model for this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigs are one of the most sensitive animals, OTA is frequently detected in various pork products made from pig organs such as the kidneys and livers. [ 5 ] How to prevent pigs from being violated by OTA exposure has become a common issue faced by farmers all over the world. Thus, we choose the porcine kidney 15 (PK‐15) cells as the cell model for this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, OTA is commonly detected in pork products, especially in the kidney and liver. [ 5–7 ] Hence, keeping pigs safe from OTA exposure is currently a pressing question for humans to resolve.…”
Section: Introductionmentioning
confidence: 99%
“…OTA production in grapes and grape-derived products is a severe problem in the wine production field, especially in European countries where the climate conditions favor the growth of ochratoxigenic Aspergillus species. Thus, since March 2002, maximum OTA levels in cereals and dried vine fruits are regulated by the EU [55,56].…”
Section: Major Mycotoxin Overviewmentioning
confidence: 99%
“…Subsequently, Frisvad et al [ 23 ] reported that other species can produce OTA: A. westerdijkiae , A. cretensis , A. flocculosus , A. roseoglobulosus , A. pseudoelegans , and A. sulphurous . Among OTA-producing Penicillium spp., P. verrucosum and P. nordicum colonize the surface of dry-cured hams during the ripening stage, and were the first OTA-producing fungal species to be identified [ 24 , 25 ]. Then, P. commune and P. chrysogenum were determined to be OTA producers [ 26 , 27 ].…”
Section: Ota-producing Fungi In Dry-cured Hamsmentioning
confidence: 99%